Analysis of the Behaviour of Immunoglobulin G Antibodies in Children and Adults Convalescing From Severe Acute Respiratory Syndrome-Coronavirus-2 Infection - Horacio Márquez-González; Briceida López-Martínez; Israel Parra-Ortega; Daniela de la Rosa-Zamboni; Marcela Salazar-García; Victor Olivar-López; Miguel Klünder-Klünder (Frontiers Media S.A., 2021)
The pandemic caused by SARS CoV-2 (COVID-19) has affected millions of people since 2020. There are clinical differences and in mortality between the adult and paediatric population. Recently, the immune response through the development of antibodies has gained relevance due to the risk of reinfection and vaccines' development.Objective: Was to compare the association of clinical history and the clinical presentation of the disease with the development of IgG antibodies against SARS-CoV-2 in paediatric and adult patients with a history of positive reverse transcriptase-polymerase chain reaction (RT-PCR) results.Methods: Cross-sectional observational study carried out in a Paediatric Hospital in Mexico City included patients under 18 years of age and health personnel with positive RT-PCR for COVID-19 comparing antibody expression. The development of specific IgG antibodies was measured, the presence of comorbidities, duration, and severity of symptoms was determined.Results: Sixty-one subjects (20 < 18 years and 41 > 18 years) were analysed. The median sample collection was 3 weeks. There were no differences in the expression of specific antibodies; no differences were shown according to the symptoms' severity. A positive correlation (r = 0.77) was demonstrated between the duration of symptoms and antibody levels.Conclusions: In conclusion, there is a clear association between the duration of the symptoms associated with SARS-CoV-2 infection and the IgG units generated in paediatric and adult patients convalescing from COVID-19.